IMPLEMENTASI PENDIDIKAN ISLAM DAN PENDIDIKAN MULTIKULTURAL PADA PESERTA DIDIK - Permana, Dian; Ahyani, Hisam (Jurnal Tawadhu, 2020)
The Indonesian nation consists of various kinds of tribes, cultures and regional languages, this reality positively illustrates the wealth of a pluralist type of society. But in this case it also saves potential conflicts that can threaten the life of the nation and state. This has been proven in several regions of Indonesia where conflicts have occurred, such as in Sampit (between Madurese and Dayaks), in Poso (between Christians and Muslims), in Aceh (between GAM and RI), or fights that often occur between villages in several regions in Java Island and inter-school student fights. To minimize the above, students must instill the values of Islamic Education in schools. With this Islamic education between groups will know and apply a sense of togetherness, tolerance, and being able to adapt to various differences. In addition to Islamic education, students must be invested in multicultural education, which is a process of cultivating a way of life that respects, sincerely, and is tolerant of the diversity of cultures that live in the midst of a pluralistic society.